The Relationship Between Coach Leadership Style and Self Confidence of University Martial Arts Athletes - Suzane Jawi; Komarudin; Mochamad Yamin Saputra; Geraldi Novian; Selmia Pasang (Universitas Tadulako, 2026)
How well a martial artist performs under pressure depends heavily on their self-confidence. For university students, building this confidence is even harder. They have to balance heavy academic workloads with intense athletic goals constantly. Because of this “dual-career” stress, a coach’s leadership style becomes very important for the athlete’s mental state. Therefore, this study examines how a coach’s leadership relates to the self-confidence of college-level martial artists. We used a quantitative correlational method and gathered data from 21 university martial arts athletes. To measure the variables, we used a coaching leadership questionnaire and an adapted self-confidence scale. Both tools showed good reliability for our specific group. The data were then processed using the Pearson correlation test in SPSS 30. Based on the analysis, there is a very strong and positive link between how a coach leads and how confident the athletes feel (r = 0.957, p < 0.001). Even though this correlation is high, we must interpret it carefully because of the small sample size and similar backgrounds of the participants. Theoretically, these results contribute to sports psychology by showing that coaches serve as a mental shield for student-athletes. It also shows that standard leadership models apply well to university combat sports a group often ignored in many studies. In practice, we suggest that coaches focus more on giving support and clear, positive feedback. Doing so will directly help keep the athletes’ confidence strong and steady.